2020
DOI: 10.1177/0030727020930039
|View full text |Cite
|
Sign up to set email alerts
|

Food security issues in the former Yugoslav countries

Abstract: Food insecurity creates serious ethical, economic, and stability problems in all countries of the world, resulting in a need for its research. Each country seeks to ensure the highest degree of self-sufficiency in meeting the food needs by its own food production. However, the production of a sufficient quantity of food, and in particular its adequate structure, is not always fully realized. Therefore, ensuring food security has become an issue of primary strategic importance. Given that all the countries of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(33 reference statements)
2
4
0
1
Order By: Relevance
“…This paper's results are in line with results in previous research on this issue [22][23][24]. The research results showed significant differences among analyzed countries in terms of food security levels [22] and, as the main indicator of discrepancy stands out GDP per capita [23,24]. Thus, the creation of adequate strategies and policies is necessary to increase food security [24].…”
Section: Migrant Crisissupporting
confidence: 88%
See 2 more Smart Citations
“…This paper's results are in line with results in previous research on this issue [22][23][24]. The research results showed significant differences among analyzed countries in terms of food security levels [22] and, as the main indicator of discrepancy stands out GDP per capita [23,24]. Thus, the creation of adequate strategies and policies is necessary to increase food security [24].…”
Section: Migrant Crisissupporting
confidence: 88%
“…Thus, key aspects of integrating Western Balkan countries to the EU that push these countries to adapt their agricultural policies to the CAP are the accession negotiation pressures and EU IPARD support [46]. This paper's results are in line with results in previous research on this issue [22][23][24]. The research results showed significant differences among analyzed countries in terms of food security levels [22] and, as the main indicator of discrepancy stands out GDP per capita [23,24].…”
Section: Migrant Crisissupporting
confidence: 87%
See 1 more Smart Citation
“…Using a set of indicators, the authors concluded that the greatest negative impact on the food system had a low level of gross domestic product per capita and corruption in the analyzed period. The research of the food security in the former Yugoslavia countries, authored by Kovljenić and Raletić-Jotanović [24], discussed that the highest level of food security is in Slovenia, and the lowest in Bosnia and Herzegovina. The key factors were: Level of economic development, population growth, international trade, and investment in the agriculture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Food insecurity/security is closely linked to the number of undernourishment. Undernourishment is the result of the absence of one or more factors contributing to good nutrition (Kovljenić & Raletić-Jotanović, 2020). One of the priorities of each country is to improve food production, ensure food security and high quality, as well as draw attention to the importance of a healthy diet, which is an integral part of preserving and improving health and disease prevention (Radosavljević, 2010: 131).…”
Section: Introductionmentioning
confidence: 99%